2017
DOI: 10.3390/su9101801
|View full text |Cite
|
Sign up to set email alerts
|

Consequential Implications of Municipal Energy System on City Carbon Footprints

Abstract: Climate change mitigation is an important goal for cities globally. Energy production contributes more than half of the global greenhouse gas emissions, and thus the mitigation potential of local municipal energy systems is important for cities to recognize. The purpose of the study is to analyze the role of local municipal energy systems in the consumption-based carbon footprint of a city resident. The research supplements the previous carbon footprint assessments of city residents with an energy system impli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…In particular local renewable energy production is promoted (Kyrö et al 2012, Li et al 2015, Maraseni et al 2016a. Several authors highlight that cleaner energy production not only reduces the CBCF of the city residents, but that the benefits spread outside the city region as well when the goods and services produced within the city are consumed by the residents of other areas (Hu et al 2016, Laine et al 2017, Lin et al 2017. Chen et al (2018) stress the importance of making the leap into renewable energy production, since smaller steps, such as investments into new energy-efficient coal power, cause infrastructure lock-ins for decades.…”
Section: City Policiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular local renewable energy production is promoted (Kyrö et al 2012, Li et al 2015, Maraseni et al 2016a. Several authors highlight that cleaner energy production not only reduces the CBCF of the city residents, but that the benefits spread outside the city region as well when the goods and services produced within the city are consumed by the residents of other areas (Hu et al 2016, Laine et al 2017, Lin et al 2017. Chen et al (2018) stress the importance of making the leap into renewable energy production, since smaller steps, such as investments into new energy-efficient coal power, cause infrastructure lock-ins for decades.…”
Section: City Policiesmentioning
confidence: 99%
“…The global reach of city footprints requires urban planning and policies to go beyond local issues and adopt a global perspective (Chen et al 2016b, Athanassiadis et al 2016. At the same time, it is equally important to make research and methods applicable at the municipal level in order to enhance their usability (Laine et al 2017). This issue has also been highlighted in the broader literature on urban carbon footprints (Lazarus et al 2013, Lin et al 2015, Ramaswami et al 2017.…”
Section: Directions Of Future Researchmentioning
confidence: 99%
“…As presented in studies such as [14][15][16][17][18], the results showed that the choice of assessment method and boundaries greatly affects GHG emission and emission implication results. The assessment method can even determine whether the implications are positive or negative.…”
Section: Discussionmentioning
confidence: 99%
“…These two approaches can thus lead to completely different perceptions of the matter and ALCA, thus misleading policy makers [16]. Especially in the electricity grid, the CLCA approach increases the GHG implications [17] and has also emphasized effects on cities' carbon footprints [18].…”
Section: Introductionmentioning
confidence: 99%
“…With China's rapid urbanization process, massive and extensive construction materials are aggregated as housing stock in urban areas. Cities have become hot spots for consuming global energy and generating global carbon emissions [17][18][19], and are therefore playing an increasingly important role in implementing greenhouse gas (GHG) mitigation policies and actions [17,[20][21][22][23]. Xiamen is one of China's low-carbon pilot cities, dedicated to exploring the way toward a low-carbon transition, and buildings comprise one of the most important sectors needing attention [24].…”
Section: Introductionmentioning
confidence: 99%